COMMUNITY EMPOWERMENT AS A FORM OF COMMUNITY SOCIAL RESILIENCE FACING THE IMPACT OF COVID-19 - Rupita - Rupita (Universitas Padjadjaran, 2020)
Small business group Usaha Bersama is commanded by PKK mothers in Sungai Bundung Laut Village, Sungai Kunyit District, Mempawah Regency. This business group empowers women in the village in producing cloth masks and disinfectants during the Covid-19 pandemic. The production of masks and disinfectant liquids is carried out together by taking advance training from competent personnel from the village officer. This research uses a descriptive qualitative approach, with analytical data being the primary data obtained by interviews and observations. Then, secondary data is obtained through review literature sourced from online news, scientific journals and books. The focus of the study is the empowering process of people with their own initiatives. The findings in this study show that this Covid-19 pandemic hit society to the lower classes, therefore in doing economic resilience their families take advantage of business opportunities namely the manufacture of disinfectants and the production of cloth masks. All of their sales were made as support for the family economy during the Covid-19 pandemic. The community groups in Sungai Bundung Laut village managed to get out of the situation of fear of Covid-19 by running productivity. All of their sales were made as support for the family economy during the Covid-19 pandemic. This business group is also a means of social resilience of the community in empowering the community through small businesses. The empowering of this group relies on local social capital that builds up between communities.